2008
DOI: 10.1111/j.1083-6101.2008.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Features of Online Newspapers: Identifying Patterns and Predicting Use of Engaged Readers

Abstract: This study seeks to identify 1) categories of interactivity, which are promoted through different types of interactive features, 2) patterns of online newspaper readers' uses of interactive features, and 3) factors, if any, that predict the use of different types of interactive features. Based on an online survey of 542 respondents, four categories of interactive features were identified. Findings show that interactive features are generally used infrequently, especially the features that facilitate human-to-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
148
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(177 citation statements)
references
References 38 publications
6
148
1
6
Order By: Relevance
“…but also striking differences. These differences in general and temporal characteristics possibly reflect the credibility of the news organisation, the interactive features they provide on their web sites, and their readers' demographics [2].…”
Section: Temporal Cycles Of News Commentsmentioning
confidence: 99%
“…but also striking differences. These differences in general and temporal characteristics possibly reflect the credibility of the news organisation, the interactive features they provide on their web sites, and their readers' demographics [2].…”
Section: Temporal Cycles Of News Commentsmentioning
confidence: 99%
“…Two such types that frequently appear in the research available are human and medium interactivity (e.g., Bucy, 2004;Chung, 2008;McMillan, 2002b). Human interactivity refers to diverse facilitations of user-to-user-interaction, such as chat rooms and message boards.…”
Section: Chung's Typology Of Interactive Featuresmentioning
confidence: 99%
“…In a recent article, Chung (2008) opted for a perceived view of interactivity when studying patterns of online newspaper readers' uses of interactive features. Providing empirical data, Chung showed that her respondents not only identified human and medium interactive features, but also combinations of the two.…”
Section: Chung's Typology Of Interactive Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being separated by physical distance, social media users are connected with each other through similar interests, and content can be spread across the world within minutes. Social media also differs from traditional media in that audiences can customize content choices and interact with others (Chung, 2008). Marketing professionals recognize that advertisements shared among friends on social media Show more significant effects on brand awareness and purchase intent than the traditional marketing tools (Lee, 2010).…”
mentioning
confidence: 99%